SISTEM TRACKING REPORT BERBASIS WEBSITE PADA PT CARDIG INTERNATIONAL SUPPORT - Betesda Betesda; Jehan Saptia Kurmia (Fakultas Ilmu Komputer dan Desain - Unsurya, 2024)
PT.Cardig International Support Textile Industry is having problems, the total lead time delays due to the production process because of no system that can track and report stages of the production process. Thus requiring a report tracking system that can resolve the production process of the problem. The method used is an experimental method to design an information system by using uml diagrams to design object and php-mysql programming language for application creation. Results from this study is the creation of a tracking system application reports that the production process can reduce total lead time delay process production and can trace and report stages of production occurring so as to know which processes are having problems or experiencing delays. The control method for all existing orders is sufficient to meet the demand for product delivery times (Delivery On Time) to customers and the facilities used to control all existing orders are sufficient to support and optimal in their use, and the Tracking Report system can help overcome Lead Time and Delivery On Time problems.